Early pathogenesis during infectious bursal disease in susceptible chickens is associated with changes in B cell genomic methylation and loss of genome integrity. (August 2017) - Ciccone, Nick A.; Smith, Lorraine P.; Mwangi, William; Boyd, Amy; Broadbent, Andrew J.; Smith, Adrian L.; Nair, Venugopal
Abstract: We propose a model by which an increase in the genomic modification, 5-hydroxymethylcytosine (5hmC), contributes to B cell death within the chicken bursa of Fabricus (BF) infected with infectious bursal disease virus (IBDV). Our findings indicate that, following an IBDV infection, Rhode Island Red (RIR) chickens have fewer surviving B cells and higher levels of 5hmC in the BF than the more resistant 15l line of birds. Elevated genomic 5hmC levels within the RIR BF are associated with markers of immune responses: infiltrating T cells and increased expression of CD40L, FasL and iNOS. Such changes correlate with genomic fragmentation and the presence of IBDV capsid protein, VP2. To explore the effects of CD40L, the immature B cell line, DT40, was exposed to recombinant chicken CD40L that resulted in changes in nuclear 5hmC distribution. Collectively, our observations suggest that T cell infiltration exacerbates early immunopathology within the BF during an IBDV infection contributing to B cell genomic instability and death to facilitate viral egress and immunosuppression. Graphical abstract: Highlights: Genomic 5-hydroxymethylation (5hmC) is studied in the context of susceptible and resistant IBDV chickens. Increased T-cell infiltration is associated with 5hmC in infected tissue. 5hmC correlates with cell death and the presence of IBDV protein, VP2. T-cell CD40L could contribute to B-cell death through a 5hmC dependent mechanism.